1985
DOI: 10.1042/bj2260105
|View full text |Cite
|
Sign up to set email alerts
|

An inhibitor of ornithine decarboxylase in the thymus and spleen of dexamethasone-treated rats

Abstract: A marked decrease in activity of ornithine decarboxylase in thymus and spleen occurs soon after treatment of rats with a glucocorticoid. In the present study, evidence was obtained that extracts of these tissues prepared 5 h after administration of dexamethasone, when the enzyme activity is very low, contain an inhibitor of ornithine decarboxylase. The inhibitor is also present at 12 h after treatment and, in lesser amount, at 2.5 h, but was not evident at 24 h. The inhibitory activity was destroyed by treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
1

Year Published

1987
1987
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 36 publications
1
3
0
1
Order By: Relevance
“…(2) its inhibitory effect on ODC can be reversed by antizyme inhibitor; (3) its Mr (26000) agrees reasonably with reported values for antizymes from a variety of sources, such as rat liver (Heller et al, 1976;Fujita et al, 1984;Kitani & Fujisawa, 1984), mouse kidney (Hayashi et al, 1986), H-35 cells (Fong et al, 1976), L-1210 and mouse neuroblastoma cells (Heller et al, 1976), RK13 rabbit kidney cells (Murakami et al, 1986) and rat lymphoma cells (Richards et al, 1986), although antizymes of Mr 50000-90000 have also been found in rat thymus (Bishop et al, 1985), rat mammary gland (Hu & Brosnan, 1987) and rat lymphoma cells (Richards et al, 1986). Although we did not examine another important criterion for antizyme, namely its inducibility by polyamines (Fong et al, 1976), Laitinen et al (1985b) observed that intraventricular administration of spermine caused some increase in the amounts of free and total antizyme activities in mouse brain.…”
Section: Discussionsupporting
confidence: 86%
“…(2) its inhibitory effect on ODC can be reversed by antizyme inhibitor; (3) its Mr (26000) agrees reasonably with reported values for antizymes from a variety of sources, such as rat liver (Heller et al, 1976;Fujita et al, 1984;Kitani & Fujisawa, 1984), mouse kidney (Hayashi et al, 1986), H-35 cells (Fong et al, 1976), L-1210 and mouse neuroblastoma cells (Heller et al, 1976), RK13 rabbit kidney cells (Murakami et al, 1986) and rat lymphoma cells (Richards et al, 1986), although antizymes of Mr 50000-90000 have also been found in rat thymus (Bishop et al, 1985), rat mammary gland (Hu & Brosnan, 1987) and rat lymphoma cells (Richards et al, 1986). Although we did not examine another important criterion for antizyme, namely its inducibility by polyamines (Fong et al, 1976), Laitinen et al (1985b) observed that intraventricular administration of spermine caused some increase in the amounts of free and total antizyme activities in mouse brain.…”
Section: Discussionsupporting
confidence: 86%
“…Thus, antizymes of 50 kDa have been reported to be present in rat thymus [150] and mammary gland [151], and even antizyme of 90 kDa was observed in lymphoma cells [152]. Northern-blot analysis indicated that thymus extract contained a single hybridizable antizyme mRNA of a size identical with that of rat liver antizyme mRNA [73].…”
Section: Unsolved Problemsmentioning
confidence: 97%
“…Earlier results showed that the pharmacological dose of corticosterone or cortisol produced a rapid and significant decrease in ornithine decarboxylase (ODC) and S -adenosyl-L-methionine decarboxylase activities in the thymus of adult rats [48][49][50] . These biosynthetic polyamine decarboxylases are known to be located only in the lymphocytes of the thymus [43] .…”
Section: Discussionmentioning
confidence: 98%
“…These biosynthetic polyamine decarboxylases are known to be located only in the lymphocytes of the thymus [43] . A marked decrease in ODC activity in the thymus and spleen occurs soon after administration of dexamethasone to rats [49][50][51] . The formation of an ODC inhibitor is an early event in lymphoid tissues in response to dexamethasone, causing the marked decrease of ODC activity, which may be the important reason for the inhibition of cell division that precedes the destruction of lymphocytes [19, 48 -51] .…”
Section: Discussionmentioning
confidence: 99%